The sociology of aging a social problems perspective - Matcha, Duane A. (Boston Allyn and Bacon, 1997)
Examines the aging process from a sociological perspective rather than a multidisciplinary one. Utilizing a social problems approach, this book examines how aging is a social construct, rather than a specific chronological age or set of conditions, and how aging is a consequence of various social structural factors, rather than a cause.
1. Growing older: a sociological explanation -- 2. Two realities: demography and aging -- 3. The view from the tower: theoretical perspectives -- 4. Society, socialization, and stereotypes -- 5. Family relationships among the elderly -- 6. Aging in a changing economy -- 7. Aging and health care -- 8. Aging and the political process -- 9. Double jeopardy/triple jeopardy -- 10. Living arrangements -- 11. Victims and criminals -- 12. Death and dying -- 13. A reassessment: aging in America.
PI-8360 donated by Department of Global Development Cornell University Ithaca.
Keywords: Gerontology -- United States; Older people -- United States